APPLICATION OF FUZZY PRINCIPAL COMPONENT ANALYSIS FOR THE BEST ALTERNATIVE TOURIST ATTRACTION IN YOGYAKARTA - Aditya Rizq Herlandy Karjawan; Muhammad Muhajir (Universitas Islam Negeri Imam Bonjol Padang, 2023)
One of the regions in Indonesia that depends on the tourism sector is the Special Region of Yogyakarta Province. The Province of the Special Region of Yogyakarta itself every year becomes a tourist destination province for vacations, many tourists do not know which places are the best choices for tourists. Therefore, this research aims to make it easier for tourists to obtain information on the best tourist spots in the Province of the Special Region of Yogyakarta. Based on the data obtained from the results of distributing online questionnaires during June 2022 – July 2022. The results of the study using the Fuzzy Principal Component Analysis method, it was found that the best tourist attraction is the Prambanan Temple tourist attraction with a PCA score of 0.677057 which means that Prambanan Temple becomes a tourist attraction. The most sought after by tourist visitors, followed by the Malioboro Street Area with a PCA score of 0.48146 and Parangtirtis Beach with a PCA score of 0.369162. The results of this study are expected to help tourists determine